Internet Addictive Individuals Share Impulsivity and Executive Dysfunction with Alcohol-Dependent Patients - Zhou, Zhenhe; Zhu, Hongmei; Li, Cui; Wang, Jun (Frontiers in Behavioral Neuroscience, 2014)
Internet addiction disorder (IAD) should belong to a kind of behavioral addiction. Previous studies indicated that there are many similarities in the neurobiology of behavior and substance addictions. Up to date, although individuals with IAD have difficulty in suppressing their excessive online behaviors in real life, little is known about the patho-physiological and cognitive mechanisms responsible for IAD. Neuropsychological test studies have contributed significantly to our understanding of the effect of IAD on the cognitive function. The purpose of the present study was to examine whether Internet addictive individuals share impulsivity and executive dysfunction with alcohol-dependent individuals. Participants include 22 Internet addictive individuals, 22 patients with alcohol dependence (AD), and 22 normal controls (NC). All participants were measured with BIS-11, go/no-go task, Wisconsin Card Sorting Test, and Digit span task under the same experimental condition. Results showed that Barratt impulsiveness scale 11 scores, false alarm rate, the total response errors, perseverative errors, failure to maintain set of IAD and AD group were significantly higher than that of NC group, and hit rate, percentage of conceptual level responses, the number of categories completed, forwards scores, and backwards scores of IAD and AD group were significantly lower than that of NC group, however, no differences in above variables between IAD group and AD group were observed. These results revealed that the existence of impulsivity, deficiencies in executive function and working memory in an IAD and an AD sample, namely, Internet addictive individuals share impulsivity and executive dysfunction with alcohol-dependent patients.